Onskuldige slagoffers? Eksegeties-homiletiese kanttekeninge by 1 Petrus 4:12-19 en 5:6-11 - Mouton, E (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
1 Peter reminds its implied audience of their paradoxical identity in Jesus Christ, while encouraging them to persevere under circumstances of affliction because they share in Christ’s suffering. The thrust of the text is determined by the oxymoron οá½»τος á¼”στ καá½¶ υἱὸς ὑψá½·σ (1:1), which describes the recipients’ position in Christ socio-rhetorically. The article explores the ethical implications of this position as articulated in pericopes 4:12-19 and 5:6-11. To suffer because of the name of Christ (4:14), and in a way that would glorify God (4:11, 16; 5:10) is – according to the perspective of 1 Peter – a blessing and honour, a gift of God’s Spirit. It is – after the example of Christ – a radical calling to holiness (1:15-16; 2:5), nonretaliation (2:23; 3:8-18), and obedient submission to a caring God who judges righteously (1:17; 2:23; 5:6-7). (Re)interpreting this text in a patriarchal environment would require particular hermeneutical and pastoral sensitivity so as not to expect further (unnuanced) submission from those whom society has already acculturated into self-sacrifice and inferiority.